Crosstalk and EMI on microwave circuit boards - Rider, Todd William (Kansas State University, 2017)
Crosstalk and electromagnetic interference (EMI) are constant problems in the design of RF circuits. There have been several studies to analyze and improve isolation of transmission lines, but the focus has been mainly on digital circuits or the isolation goals have been on the order of 40-60 dB. When the isolation goals are much more stringent, such as 80-100 dB, much of a designer’s time is still spent ensuring that a circuit meets isolation and EMI constraints. This typically involves the use of extensive metal shielding over a circuit board. This thesis presents results from an isolation and EMI study to provide a simple reference that can be applied to typical substrates, provided proper scaling is used between substrates. The results in this thesis are reported from DC to 30 GHz using a low cost 4-layer FR4 process. The changes in isolation between various transmission lines types are investigated while varying line separation and length. It is shown that isolation between ground-backed coplanar waveguide (GBCPW) and stripline traces can reach 100dB through L-band and 60dB through Ku-band for 1.3in traces separated by 150mils. Due to the heavy usage of filters in RF design, the isolation between edge-coupled bandpass filters is also studied. It is seen that isolation levels of 100dB through L-band by enclosing the filters within stripline technology is possible, provided that signal launches and layer transitions are carefully designed. Within the passband of the 20 GHz filter tested, the isolation is less but is still significantly improved by use of enclosed stripline. Lastly, a preliminary assessment of EMI is presented which focuses on radiation levels as well as variables that can degrade isolation performance. The data illustrated in this thesis can provide guidance in the early stages of RF circuit design to determine appropriate structures to meet given design requirements. It also helps to assess the degree to which additional metal shielding can be avoided in PC board systems that use multi-layer technologies.
Keywords: Crosstalk; Electromagnetic Interference; Isolation; Coupling; Shielding